The CCR4-NOT Complex Maintains Stability and Transcription of rRNA Genes by Repressing Antisense Transcripts - Hosoyamada, Shun (Mol Cell Biol, 2019)
The rRNA genes (rDNA) in eukaryotes are organized into highly repetitive gene clusters. Each organism maintains a particular number of copies, suggesting that the rDNA is actively stabilized. We previously identified about 700 Saccharomyces cerevisiae genes that could contribute to rDNA maintenance. Here, we further analyzed these deletion mutants with unstable rDNA by measuring the amounts of extrachromosomal rDNA circles (ERCs) that are released as by-products of intrachromosomal recombination. We found that extremely high levels of ERCs were formed in the absence of Pop2 (Caf1), which is a subunit of the CCR4-NOT complex, important for the regulation of all stages of gene expression. In the pop2 mutant, transcripts from the noncoding promoter E-pro in the rDNA accumulated, and the amounts of cohesin and condensin were reduced, which could promote recombination events. Moreover, we discovered that the amount of rRNA was decreased in the pop2 mutant. Similar phenotypes were observed in the absence of subunits Ccr4 and Not4 that, like Pop2, convey enzymatic activity to the complex. These findings indicate that lack of any CCR4-NOT-associated enzymatic activity resulted in a severe unstable rDNA phenotype related to the accumulation of noncoding RNA from E-pro.